Amanah Dan Akuntabilitas Dalam Al-Quran: Relevansinya Dengan Manajemen Sdm Pendidikan Islam - Neneng Kurnia; Susanto Susanto (Journal of Innovative and Creativity, 2026)
This discussion describes the concepts of trust and accountability in the Qur'an and its relevance to the management of human resources (HR) of Islamic education. Trust is understood as a moral and professional responsibility that is carried out with integrity, while accountability emphasizes the obligation to account for every action and decision. The integration of these values becomes the ethical and operational foundation in the management of Islamic education human resources that are oriented towards quality, professionalism, and character. The Ulumul Qur'an approach is used to understand Quranic values contextually so that they can be actualized in the practice of institutional management of Islamic education. The results show that the internalization of trust and accountability plays an important role in building a responsible work culture, improving the quality of human resources, and supporting the achievement of Islamic education goals in a holistic and sustainable manner